Memorandum: Letter to Todd Johnson from Sam Matchett, August 18, 1983 - Houseal, Willie H. (Valdosta State University Archives and Special Collections, 1983)
The letter, dated August 18, 1983, is written by Todd Johnson the lead Council on the Valdosta Civil Action case, to Sam Matchett a summer intern. The document details voting strategy based on a conversation between Todd Johnson and a councilmen from Milledgeville.
1 electronic document, PDF, 2 scanned images
Keywords: Valdosta (Ga.); Lowndes County (Ga.); City council members; Milledgeville (GA.)